Kesan Pembaharuan Pusat Membeli-Belah Terhadap Aktiviti Perniagaan - Zulkifli, Fathin Nadia; Yaacob, Mat Tawi (Research in Management of Technology and Business, 2020)
Shopping malls are an important element in enhancing the development and economic development of a country. However some are unable to withstand the challenging business competition. This study focuses on The Mall shopping mall, Kuala Lumpur with the aims to look at redevelopment strategies and remarketing models after falling behind previously. This was done through a qualitative approach by interviewing stakeholders; its management as well as traders. The findings show that changes in the redevelopment concept, the change in building’s external facade and interior forms, accessibility and security aspects play a role in re-entering into commercial business competition. With the onset of the Covid-19 pandemic, it provides an opportunity for further research to see its impact on physical shopping malls.